2014
DOI: 10.1016/j.yexmp.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in intrahepatic cholangiocarcinoma: Pathobiological insights and clinical implications

Abstract: Periostin is a modular glycoprotein frequently observed to be a major constituent of the extracellular milieu of mass-forming intrahepatic cholangiocarcinoma and other desmoplastic malignant tumors. In intrahepatic cholangiocarcinoma, as well as in desmoplastic pancreatic ductal adenocarcinoma, periostin is overexpressed and hypersecreted in large part, if not exclusively, by cancer-associated fibroblasts within the tumor stroma. Through its interaction with specific components of the extracellular tumor matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 87 publications
0
44
0
Order By: Relevance
“…While there have been many studies carried out on the functions of Msln and Postn, their role in cancer progression, including that of ICC, remains unclear and needs to be elucidated 8, 34, 40. Based on the data described herein, we propose that our unique rat cholangiocarcinoma models are ideal preclinical platforms for investigating Postn and Msln biology, regulation and functional relationships in the context of α‐SMA + CAF and cancer cell interactions promoting ICC progression, and the potential of Postn and Msln as molecular targets for ICC therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been many studies carried out on the functions of Msln and Postn, their role in cancer progression, including that of ICC, remains unclear and needs to be elucidated 8, 34, 40. Based on the data described herein, we propose that our unique rat cholangiocarcinoma models are ideal preclinical platforms for investigating Postn and Msln biology, regulation and functional relationships in the context of α‐SMA + CAF and cancer cell interactions promoting ICC progression, and the potential of Postn and Msln as molecular targets for ICC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the matricellular glycoprotein periostin (Postn) and the glycosylphosphatidylinositol‐anchored cell membrane glycoprotein mesothelin (Msln) have each been independently suggested as having potential as prognostic factors for human ICC 6, 7. Each may also provide opportunities for the development of novel targeted therapies for ICC 8, 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dismal prognosis and aggressive progression associated with ICC have led researchers and clinicians to explore new avenues of potential treatment for ICC patients 58, 59, 60. Increasing evidence demonstrated that miRNAs are involved in important biological processes, including cell proliferation, differentiation, migration, invasion and apoptosis 61, 62, 63, 64, 65.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Thus, AHR and its ligands may be potentially valuable components to target in the treatment of cholangiocarcinoma. The integrin family has long been studied as having a potential role in the regulation of cholangiocarcinoma (CCC) [10][11][12]. Numerous studies have determined that specific integrins may activate the tumor progression and invasion of CCC [10,11].…”
mentioning
confidence: 99%